Aneurysm Growth After Endovascular Sealing of Abdominal Aortic Aneurysms (EVAS) with the Nellix Endoprosthesis. (November 2020) - Yafawi, Asma; McWilliams, Richard G.; Fisher, Robert K.; England, Andrew; Karouki, Maria; Uhanowita Marage, Ruwanka; Torella, Francesco
Abstract : Objective: The aim of this study was to measure the incidence of post endovascular aneurysm sealing (EVAS) abdominal aortic aneurysm (AAA) growth, and its association with stent migration, in a cohort of patients with differing compliance to old and new Instructions For Use (IFU). Methods: A retrospective single centre study was conducted to review the computed tomography (CT) and clinical data of elective, infrarenal EVAS cases, performed as a primary intervention, between December 2013 and March 2018. All included patients had a baseline post-operative CT scan at one month and at least one year follow up. The primary outcome measure was the incidence of AAA growth and its association with stent migration. AAA growth was defined as a ≥5% increase in aortic volume between the lowermost renal artery and the aortic bifurcation post EVAS at any time during follow up, in comparison to the baseline CT scan. Migration was defined according to the ESVS guidelines, as > 10 mm downward movement of either Nellix stent frame in the proximal zone. Results: Seventy-six patients were eligible for inclusion in the study (mean age 76 ± 7.4 years; 58 men). AAA growth was identified in 50 of 76 patients (66%); adherence to IFU did not affect its incidence (mean growth within IFU-2016 compliant cohort vs. non-compliant: 16% vs. 13%, p = .33). Over time, the incidence of AAA growth increased, from 32% at one year to 100% at four years. AAA growth by volume was progressive ( p < .001), as its extent increased over time. Migration was detected in 16 patients and there was a statistically significant association with AAA growth (13 patients displayed migration and AAA growth, p = .036). Conclusion: Patients treated with EVAS are prone to AAA growth, irrespective of whether their aortic anatomy is IFU compliant. AAA growth by volume is associated with stent migration. Clinicians should continue close surveillance post EVAS, regardless of whether patients are treated within IFU.